Preparation method of regenerated lithium iron phosphate positive electrode material, prepared positive electrode material and application thereof
By using ethanol and Zr elements in the recycling process of the positive electrode material of waste lithium iron phosphate batteries, and using hydrothermal method and sintering method, the resource waste, environmental pollution and high cost problems existing in traditional recycling methods are solved, and high performance and low cost are achieved regeneration of the cathode material.
Patent Information
- Application Number
- CN202510043266.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has problems of resource waste, environmental pollution and high costs when recycling waste lithium iron phosphate battery positive electrode materials, and traditional methods are not suitable for large-scale regeneration.
Ethanol is used as a solvent and reducing agent, lithium source and Zr elements are added, and the positive electrode material of waste lithium iron phosphate battery is recovered through hydrothermal method and sintering method, which inhibits the failure of the material surface and enhances the stability and electrochemical reversibility of the material.
The direct regeneration of the positive electrode material of waste lithium iron phosphate battery is achieved, which improves the performance and life of the material, reduces the reverse dissolution of lithium, reduces the loss of oxygen, and enhances the stability of the structure.
Smart Images

Figure CN119430124A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a regenerated lithium iron phosphate positive electrode material, the prepared positive electrode material and its application, and belongs to the field of battery material recycling. Background Art
[0002] With the gradual popularization of electric vehicles, a large amount of waste lithium iron phosphate (LFP) batteries will inevitably be generated in the near future. If these waste batteries are not handled properly, it will not only cause a huge waste of resources, but also have a significant impact on the environment. Since the positive electrode material is the most expensive among battery components, accounting for about 40% of the total cost of lithium batteries, it makes more sense to recycle the positive electrode than other components.
[0003] Traditional methods for large-scale treatment of waste positive electrodes of lithium batteries include hydrometallurgy and pyrometallurgy, but neither method is suitable for large-scale regeneration of batteries. Hydrometallurgy generally uses a large amount of chemical reagents (acids and alkalis) to dissolve waste lithium-ion batteries and recover precious metal elements by precipitation, which is not environmentally friendly. Recently, mechanochemical methods have also been applied to hydrometallurgy, in which ion leaching helps to reduce the use of chemicals. However, direct regeneration of the positive electrode process requires recrystallization of the crystals, and the crystal structure is expected to be relatively complete, so the mechanochemical pretreatment method may not be suitable for direct regeneration. For pyrometallurgy, the calcination process consumes a lot of energy and the recovery of lithium is very limited. More importantly, waste LFP does not contain precious metals such as cobalt and nickel, so from an economic point of view, the above methods are not suitable for recycling waste LFP. But waste LFP also contains expensive Li. Although the material cost of synthesizing LFP from raw materials is not high, the cost of the synthesis process is high. By controlling the atmosphere and temperature, the cost of direct regeneration can be effectively reduced, making the recovery of LFP valuable. Therefore, there are still many defects in the current recycling methods for lithium iron phosphate batteries, and improvements are urgently needed. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of this application is to provide an environmentally friendly, effective and low-cost direct regeneration method for waste LFP. Using ethanol as a solvent and a reducing agent, adding a lithium source, and recycling waste LFP through a hydrothermal method and a sintering method.
[0005] Generally, the destruction of LFP occurs on the surface; therefore, suppressing the failure of the adjacent surface of LFP plays a vital role in preventing the overall failure of LFP. To this end, the present application doped the Zr element in the LFP recycling and regeneration process. The strength of the Zr~O bond is much greater than that of the Fe~O bond, which can play a pinning role, thereby suppressing the release of oxygen from the regenerated positive electrode material and enhancing the electrochemical reversibility.
[0006] This application proposes a unique strategy to achieve the regeneration of spent LFP with excellent performance by using ethanol as solvent and reducing agent and Zr doping to enhance the stability of the material.
[0007] According to one aspect of the present application, a method for preparing a regenerated lithium iron phosphate positive electrode material is provided, comprising the following steps: The lithium iron phosphate powder of the waste lithium battery positive electrode material is mixed with an ethanol solution containing a lithium source and ZrO2, reacted in a closed container to obtain a black powder, and thermally annealed in an oxidizing gas atmosphere to obtain the regenerated lithium iron phosphate positive electrode material.
[0008] The lithium source is selected from at least one of LiOH, lithium acetate and lithium sulfate.
[0009] In the ethanol solution containing the lithium source and ZrO2, the mass ratio of the lithium source to ZrO2 is 1.05-1.08:1.
[0010] The solid-to-liquid ratio of the waste lithium battery positive electrode material powder to the ethanol solution containing a lithium source and ZrO2 is 1:15-25 g / ml.
[0011] The waste lithium battery positive electrode material powder is ball milled for 3 to 5 hours.
[0012] The particle size of the waste lithium battery positive electrode material powder is 30-50 μm.
[0013] The reaction temperature is 140-160°C.
[0014] The reaction time is 11-13 hours.
[0015] The temperature of the thermal annealing is 800-900°C.
[0016] The thermal annealing time is 11 to 13 hours.
[0017] The oxidizing gas atmosphere is an oxygen atmosphere.
[0018] Optionally, the following steps are included: (1) Ball mill the waste positive electrode material powder for 4 hours to make its particles uniform and fine.
[0019] (2) It is then mixed with a saturated ethanol solution containing LiOH and ZrO2 in a certain solid-liquid ratio, stirred and heated in a closed reactor.
[0020] (3) The solution after the reaction was filtered and dried to obtain a black powder.
[0021] (4) The black powder mixture is subjected to a thermal annealing treatment in an oxygen atmosphere for a certain period of time to obtain a regenerated cathode material.
[0022] According to another aspect of the present application, a regenerated lithium iron phosphate positive electrode material is provided, which is prepared by the above-mentioned preparation method.
[0023] According to another aspect of the present application, a lithium iron phosphate battery is provided, comprising a positive electrode prepared from the above-mentioned regenerated lithium iron phosphate positive electrode material.
[0024] The beneficial effects of this application include: (1) Compared with the existing hydrothermal method, the present application uses ethanol as a solvent for lithium. The solubility of lithium in ethanol is lower than that in water, which can inhibit the reverse dissolution of lithium and make the lithium replenishment more accurate, thereby making the performance of the regenerated positive electrode material better than the lithium replenishment of the hydrothermal method. The low boiling point of ethanol is conducive to the formation of a high-pressure environment that satisfies lithium embedding, so the energy consumption is lower than that of the hydrothermal method.
[0025] (2) The technical solution of the present application is doped with Zr elements, which have stronger bond energy, so oxygen atoms or defects can be "trapped" around these elements, resulting in a reduction in oxygen atoms in the iron redox center, reducing the loss of oxygen, and thus enhancing the stability of the structure. This makes the positive electrode material prepared by the preparation method of the present application not only have excellent performance, but also have a longer life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the element distribution diagram of the regenerated lithium iron phosphate positive electrode material obtained in Example 1 of the present application.
[0027] Figure 2 The electrochemical performance of the regenerated lithium iron phosphate positive electrode material obtained in Example 1 of the present application is compared with that of commercial materials. DETAILED DESCRIPTION
[0028] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0029] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0030] Example 1 A method for recovering lithium iron phosphate from waste lithium batteries, the method comprising the following steps: (1) Ball mill the waste positive electrode material powder for 4 hours to make its particles uniform and fine.
[0031] (2) It is then mixed with a saturated ethanol solution containing LiOH and ZrO2 in a certain solid-liquid ratio, stirred and heated in a closed reactor.
[0032] (3) The solution after the reaction was filtered and dried to obtain a black powder.
[0033] (4) The black powder mixture is subjected to a thermal annealing treatment in an oxygen atmosphere for a certain period of time to obtain a regenerated cathode material.
[0034] The average particle size of the material after ball milling in step (1) is 30-50 microns.
[0035] The ball-milled material in step (2) is mixed with a saturated ethanol solution containing LiOH and ZrO2 at a solid-liquid ratio of 1:20 g mL~1.
[0036] The mixed materials in step (2) are stirred and heated at a temperature of 150° C. for 12 hours.
[0037] The black mixture in step (4) is calcined in an oxygen atmosphere at a temperature of 850° C. for 12 hours to obtain a regenerated lithium iron phosphate positive electrode material.
[0038] Figure 1 This is the element distribution diagram of the regenerated lithium iron phosphate positive electrode material obtained in Example 1 of the present application. It can be seen that the method of the present application indeed obtains the lithium iron phosphate positive electrode material.
[0039] Figure 2 The electrochemical performance of the regenerated lithium iron phosphate cathode material obtained in Example 1 of the present application is compared with that of the commercial material. It can be seen that the lithium iron phosphate cathode material obtained by the method of the present application has shown a significant advantage in specific capacity compared with the commercial lithium phosphate material after 200 cycles, and can still maintain a volume retention rate of 67.87% until 500 cycles, while the commercial lithium phosphate material can only maintain it at 41.15%.
[0040] Example 2 A method for recovering lithium iron phosphate from waste lithium batteries, the method comprising the following steps: (1) Ball mill the waste positive electrode material powder for 4 hours to make its particles uniform and fine.
[0041] (2) It is then mixed with a saturated ethanol solution containing lithium acetate (CH3COOLi) and ZrO2 in a certain solid-liquid ratio, stirred and heated in a closed reactor.
[0042] (3) The solution after the reaction was filtered and dried to obtain a black powder.
[0043] (4) The black powder mixture is subjected to a thermal annealing treatment in an oxygen atmosphere for a certain period of time to obtain a regenerated cathode material.
[0044] The average particle size of the material after ball milling in step (1) is 30-50 microns.
[0045] The ball-milled material in step (2) is mixed with a saturated ethanol solution containing CH3COOLi and ZrO2 at a solid-liquid ratio of 1:20 g mL~1.
[0046] The mixed materials in step (2) are stirred and heated at a temperature of 150° C. for 12 hours.
[0047] The black mixture in step (4) is calcined in an oxygen atmosphere at a temperature of 850° C. for 12 hours to obtain a regenerated lithium iron phosphate positive electrode material.
[0048] The electrochemical performance of the regenerated lithium iron phosphate positive electrode material obtained in Example 2 was tested, and the volume retention rate after 500 cycles was 60.96%.
[0049] Example 3 A method for recovering lithium iron phosphate from waste lithium batteries, the method comprising the following steps: (1) Ball mill the waste positive electrode material powder for 4 hours to make its particles uniform and fine.
[0050] (2) It is then mixed with a saturated ethanol solution containing lithium sulfate (Li2SO4) and ZrO2 in a certain solid-liquid ratio, stirred and heated in a closed reactor.
[0051] (3) The solution after the reaction was filtered and dried to obtain a black powder.
[0052] (4) The black powder mixture is subjected to a thermal annealing treatment in an oxygen atmosphere for a certain period of time to obtain a regenerated cathode material.
[0053] The average particle size of the material after ball milling in step (1) is 30-50 microns.
[0054] The ball-milled material in step (2) is mixed with a saturated ethanol solution containing Li2SO4 and ZrO2 at a solid-liquid ratio of 1:20 g mL~1.
[0055] The mixed materials in step (2) are stirred and heated at a temperature of 150° C. for 12 hours.
[0056] The black mixture in step (4) is calcined in an oxygen atmosphere at a temperature of 850° C. for 12 hours to obtain a regenerated lithium iron phosphate positive electrode material.
[0057] The electrochemical performance of the regenerated lithium iron phosphate positive electrode material obtained in Example 3 was tested, and the volume retention rate after 500 cycles was 55.85%.
[0058] Comparative Example 1 A method for recovering lithium iron phosphate from waste lithium batteries, the method comprising the following steps: (1) Ball mill the waste positive electrode material powder for 4 hours to make its particles uniform and fine.
[0059] (2) It is then mixed with a saturated ethanol solution containing LiOH at a certain solid-liquid ratio, stirred and heated in a closed reactor.
[0060] (3) The solution after the reaction was filtered and dried to obtain a black powder.
[0061] (4) The black powder mixture is subjected to a thermal annealing treatment in an oxygen atmosphere for a certain period of time to obtain a regenerated cathode material.
[0062] The average particle size of the material after ball milling in step (1) is 30-50 microns.
[0063] The ball-milled material in step (2) is mixed with a saturated ethanol solution containing LiOH at a solid-to-liquid ratio of 1:20 g mL~1.
[0064] The mixed materials in step (2) are stirred and heated at a temperature of 150° C. for 12 hours.
[0065] The black mixture in step (4) is calcined in an oxygen atmosphere at a temperature of 850° C. for 12 hours to obtain a regenerated lithium iron phosphate positive electrode material.
[0066] The electrochemical performance of the regenerated lithium iron phosphate positive electrode material obtained in Example 2 was tested, and the capacity retention rate after 500 cycles was 60.96%.
[0067] By comparing the comparative example with the example, it is found that under the conditions of Example 1, the discharge capacity and capacity retention rate of the regenerated lithium iron phosphate positive electrode material obtained after adding ZrO2 are significantly better than those of the comparative example.
[0068] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a regenerated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: The lithium iron phosphate powder of the waste lithium-ion battery positive electrode material is mixed with an ethanol solution containing a lithium source and ZrO2, reacted in a closed container to obtain a black powder, and thermally annealed in an oxidizing gas atmosphere to obtain the regenerated lithium iron phosphate positive electrode material.
2. The method for preparing the regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium source is selected from at least one of LiOH, lithium acetate and lithium sulfate.
3. The method for preparing the regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the ethanol solution containing the lithium source and ZrO2, the mass ratio of the lithium source to ZrO2 is 1.05-1.08:
1.
4. The method for preparing the regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The solid-to-liquid ratio of the waste lithium battery positive electrode material powder to the ethanol solution containing a lithium source and ZrO2 is 1:15-25 g / ml.
5. The method for preparing the regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle size of the waste lithium battery positive electrode material powder is 30-50 μm.
6. The method for preparing the regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The reaction temperature is 140-160°C; The reaction time is 11-13 hours.
7. The method for preparing a regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The temperature of the thermal annealing is 800-900°C; The thermal annealing time is 11 to 13 hours.
8. The method for preparing a regenerated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The oxidizing gas atmosphere is an oxygen atmosphere.
9. A regenerated lithium iron phosphate positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium iron phosphate battery, characterized in that: A positive electrode prepared from the regenerated lithium iron phosphate positive electrode material as described in claim 9.
Citation Information
Patent Citations
Novel conductive agent doping / coating lithium iron phosphate material and its production method
CN101222044A
Modified positive electrode material for lithium iron phosphate battery and preparation method of modified positive electrode material and lithium-ion battery
CN106602027A
Method for regenerating lithium iron phosphate by leaching, spray drying and solid phase method
CN110098442A
Restoration and regeneration method of waste lithium iron phosphate positive electrode material and lithium iron phosphate positive electrode material
CN114388923A
Repairing and regenerating method of waste lithium iron phosphate battery positive electrode material
CN116902953A
Cited By
Efficient direct regeneration method of failed lithium iron phosphate
CN120728063A